2017
DOI: 10.1111/wrr.12522
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and other new foot ulcers after healed plantar forefoot diabetic ulcer

Abstract: Diabetic foot ulcer is a serious complication in patients with diabetes. In most outcome studies of this condition, there is a combination of various types of ulcer and ulcer locations. Plantar ulcers are usually localized to the forefoot, and constitute a quarter of all diabetic foot ulcers. There are a limited number of studies regarding development of new ulcers following healing of a plantar forefoot ulcer, and there are no uniform definitions of recurrent and other new ulcers. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…Others define 'relapsers' as people whose ulceration had recurred at least twice [23]. As noted, we define a recurrent ulcer, as an ulcer at the same site/location as the previous ulcer, and a new ulcer as an ulcer at another location, which we find more accurate, and this definition is also used in a recent Swedish study [21]. In the present study most of the diabetic foot ulcers during followup were new (77.3%) and therefore a recurrent diabetic foot ulcer was a relatively rare event, which may be because of extra focus on the healed area by off-loading or surgery.…”
Section: Nonprogressors N=366mentioning
confidence: 79%
See 2 more Smart Citations
“…Others define 'relapsers' as people whose ulceration had recurred at least twice [23]. As noted, we define a recurrent ulcer, as an ulcer at the same site/location as the previous ulcer, and a new ulcer as an ulcer at another location, which we find more accurate, and this definition is also used in a recent Swedish study [21]. In the present study most of the diabetic foot ulcers during followup were new (77.3%) and therefore a recurrent diabetic foot ulcer was a relatively rare event, which may be because of extra focus on the healed area by off-loading or surgery.…”
Section: Nonprogressors N=366mentioning
confidence: 79%
“…A Dutch study showed a high recurrence rate of 42% in 18 months . A recent Swedish study found that 42% had a recurrent or other diabetic foot ulcer in 2 years after a healed plantar forefoot ulcer . Armstrong et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One hundred eighty‐two full‐text articles were assessed for eligibility, and 133 (65 reviews, eight studies of duplicated population, and 60 studies with data that cannot be extracted) of them were removed since they did not meet our selection criteria. Finally, 49 articles were included in our meta‐analysis after full‐text review …”
Section: Resultsmentioning
confidence: 99%
“…Previous diabetic foot ulceration constitutes the highest risk for subsequent foot ulceration in diabetes [1,9,10,12,24]. Effective foot protection to reduce re-ulceration is challenging [25].…”
Section: Discussionmentioning
confidence: 99%